The Effect of BN Reinforcement on the Mechanical Properties of Nanostructured Al2O3 Ceramics - Kim, Seong-Eun; Choi, Woo-Jin; Yoon, Jin-Kook; Shon, In-Jin (AMER SCIENTIFIC PUBLISHERS, 2020)
In spite of many attractive properties, the low fracture toughness of Al2O3 ceramic below ductile brittle transition temperature limits its wide application in industry. One of the most obvious methods to improve the fracture toughness has been to add reinforcing compounds to fabricate nanostructured composite materials. In this respect, BN was evaluated as the reinforcing agent of Al2O3 ceramics using pulsed current activated sintering (PCAS). Highly dense alumina-BN composites with a relative density of up to 100% were achieved within short periods (2 min) by PCAS under a 80 MPa pressure. The rapid sintering method allowed the retention of the nanostructure by inhibiting the grain growth. The grain size of alumina was reduced remarkably by the addition of BN. The addition of BN to Al2O3 ceramic simultaneously improved the hardness and fracture toughness of alumina-BN composite.